2005
DOI: 10.1126/science.1116505
|View full text |Cite
|
Sign up to set email alerts
|

Jumping Nanodroplets

Abstract: Flat gold nanostructures on inert substrates like glass or graphite were illuminated by single intensive laser pulses with fluences above the gold melting threshold. The liquid structures produced in this way are far from their equilibrium shape, and a dewetting process sets in. On a time scale of a few nanoseconds, the liquid contracted toward a sphere. During this contraction, the center of mass moved upward, which could lead to detachment of droplets from the surface due to inertia. The resulting velocities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(186 citation statements)
references
References 16 publications
4
173
1
1
Order By: Relevance
“…We prepare such samples by illumination of the original triangular arrangement with a two-beam interference pattern of a nslaser. Reaching the melting temperature, the particles undergo a dewetting process which leads finally to the ejection of the particles from the surface [24]. Figure 8 depicts the result of such a preparation process after three annealing steps under different angles.…”
Section: Methodsmentioning
confidence: 99%
“…We prepare such samples by illumination of the original triangular arrangement with a two-beam interference pattern of a nslaser. Reaching the melting temperature, the particles undergo a dewetting process which leads finally to the ejection of the particles from the surface [24]. Figure 8 depicts the result of such a preparation process after three annealing steps under different angles.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, pulsed-laser-induced dewetting of two-dimensional films 3-9 , one-dimensional lines and rings [10][11][12][13] , and lithographically patterned nanostructures 14,15 has demonstrated that understanding and controlling thin-film and Rayleigh-Plateau instabilities improves the ability to create organized metallic nanoparticle ensembles. Assembled particles have also been shown to "jump" or eject from one substrate and transfer to another depending on the energetics and dynamics of various laser-melted nanostructures [16][17][18] . Heretofore, the as described in the Methods section, the laser spot has a Gaussian profile and thus the radial profile of each image also contains thermal and temporal information.…”
Section: Lettermentioning
confidence: 99%
“…These findings show the importance of inertia on the movement of liquids on the nanoscale not only for the annealing of nanostructures [10] but also for inhomogeneous illuminated thin films.…”
Section: Introductionmentioning
confidence: 81%